2019
DOI: 10.1111/pace.13765
|View full text |Cite
|
Sign up to set email alerts
|

Non‐vitamin K oral anticoagulants versus warfarin for left atrial appendage thrombus resolution in nonvalvular atrial fibrillation or flutter

Abstract: Background Non‐vitamin K oral anticoagulants (NOACs) have emerged as alternatives to vitamin K antagonists in select situations. For left atrial (LA) appendage thrombus in nonvalvular atrial fibrillation (AF) or flutter, guidelines recommend oral anticoagulation (OAC) for at least 3 weeks prior to reassessment. Data comparing NOACs to warfarin in this scenario are scarce. Methods A retrospective study identified subjects with nonvalvular AF or flutter who were: a) noted to have LA thrombus detected on transeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
11
0
7
Order By: Relevance
“…Transesophageal echocardiography (TEE) is a sensitive method for identifying intracardiac thrombus 2 . As complete thrombus resolution is mandatory before AF ablation or cardioversion, it is crucial that the prescribed medication have effective anticoagulation 3 . The administration of vitamin K antagonists (VKAs), such as warfarin, has been the mainstay treatment for intracardiac thrombus, with the target international normalized ratio of 2.0 to 3.0.…”
Section: Introductionmentioning
confidence: 99%
“…Transesophageal echocardiography (TEE) is a sensitive method for identifying intracardiac thrombus 2 . As complete thrombus resolution is mandatory before AF ablation or cardioversion, it is crucial that the prescribed medication have effective anticoagulation 3 . The administration of vitamin K antagonists (VKAs), such as warfarin, has been the mainstay treatment for intracardiac thrombus, with the target international normalized ratio of 2.0 to 3.0.…”
Section: Introductionmentioning
confidence: 99%
“…LA thrombus resolution rates from smaller studies provide important preliminary data for power calculations to determine target sample sizes for such definitive studies. The limitations of our study raised by Dr Tak and colleagues will hopefully be addressed at that time.…”
mentioning
confidence: 93%
“…Retrospective cohort studies are important to build the “pyramid of evidence,” given few NOAC studies . It is our anticipation that multicenter randomized controlled trials and prospective cohort studies will ultimately address whether NOACs are reasonable, or perhaps even preferable, alternatives to warfarin for treatment of LA thrombus in nonvalvular AF or flutter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with interest a recent article comparing non‐vitamin K oral anticoagulants (NOACs) and warfarin for left atrial appendage (LAA) thrombus resolution in nonvalvular atrial fibrillation (AF) or flutter reported by Hussain et al. They concluded that in patients with nonvalvular AF or flutter who were OAC naïve at the time of LA appendage thrombus diagnosis, treatment with NOACs and warfarin for at least 3 weeks had similar rates of complete LA appendage thrombus resolution . We believe that their study is likely to form a valuable addition to the literature.…”
mentioning
confidence: 96%